Prise En Charge Des Victimes Du Conflit Armé Du Nord Mali Dans Les Hôpitaux De Niamey - Chaibou MS; James Didier L.; Daddy H.; Salissou Abou A.N.; Rhissa M.; Gagara M.; Garba I.; Coulibaly Y.; Sani R. (European Scientific Journal, ESJ, 2017)
Objectives: The aims of this study was to evaluate the management of lesions in victims of the malian conflict patients admitted to Niamey hospitals. Methods: A retrospective study was conducted in Niamey hospitals from January 1st, 2012 to December, 31th, 2013. Data collected included âge, sex, means of transport, topography of trauma, treatment and outcome. Results: The sample included fifty one (51) patients. All patients were male; the mean age was 29,5 years ± 9 years, ranging from 17-71 years. The age between 26 and 35 were most affected in 47% of cases (24 patients), soldiers represented 72.54% (37 patients); and civils 27.45% (14 patients). 74.50% of our patients (38) were been transported in Niamey by aircraft. The trauma concerned the members in 54.90% (28 cases), canio facial in 17.60% (9 cases), abdomen in 11.80% (6 cases). We observed only one polytrauma. 66.66% (34) of patients were injured by firearms, 29.41% (15) by accidents of roads, 3,93% by burn (2 patients). The lesions found were bone in 41.17% (21 patients), skin-muscle in 35.29% (18 patients), visceral in 9.80% (5 patients). Five patients died (9.80%). Conclusion: the internationalization of conflicts requires a reorganization of the care by involving all the nearness health structures in order to ensure adequate care and neutrality.